Effect of methanol extracts of nony fruit on mice infected by RH strain of Toxoplasma gondii - Subekti, Didik T; Sari, Eka S.P; Widiastuti, Dwi R; Haerlani, Rica; Fitri Diani, Eka; Iskandar, Tolibin; Laksmitawati, Dian R (Indonesian Journal of Animal and Veterinary Sciences, 2005)
Intraperitoneal infection of Type I Toxoplasma gondii on mice causes high mortality at a short time due to parasitic burden, immunosuppression, cell and tissue damage. The mice survival is increased after treated with drugs that reduce or destroy tachyzoite and modulate or recovered the immune system. Nony fruit (Morinda citrifolia) is popular as immunomudulator and has antoxoplasma properties. The purpose of this experiment is to evaluate the effect of ethanol extract of nony fruit and Fansidar® (pyrimethamine-sulfadiazine) to reduce tachyzoite and improve survival as well as immunomudulator on mice following toxoplasma infection. Mice was divided into six groups (10 mice respectively) consist of infected-non treated groups, infected + Fansidar®, infected + ethanol extract of nony on several doses (100, 50, 25%) and non infected-non treated groups. All mice on each groups were infected intraperitoneally by 5 x 106 and 2,5 x 103 RH strain of Toxoplasma gondii tachyzoite/mice respectively. The results have shown that Fansidar® was successfully to reduced tachyzoite and improved mice survival but the ethanol extract of nony fruit was failed.     Key Words: Survivality, Immunomodulator, Toxoplasma gondii, Nony extracts